2006
DOI: 10.1111/j.1440-1746.2006.04269.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of irritable bowel syndrome in Korea: Population‐based survey using the Rome II criteria

Abstract: The prevalence of IBS in the Korean population is 6.6%, and the male:female ratio is similar. Also, IBS is more frequent in younger subjects. Irritable bowel syndrome subjects visited a physician mostly due to abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
84
6
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 26 publications
10
84
6
2
Order By: Relevance
“…However, in this study; alcohol consumption, low exercise and psychological disorders were considered as risk factors for IBS not rotating shift work. The prevalence of IBS in this present study is also higher than that reported in the general population [6][7][8][9]20] .…”
Section: Discussioncontrasting
confidence: 53%
“…However, in this study; alcohol consumption, low exercise and psychological disorders were considered as risk factors for IBS not rotating shift work. The prevalence of IBS in this present study is also higher than that reported in the general population [6][7][8][9]20] .…”
Section: Discussioncontrasting
confidence: 53%
“…4 Globally, there is a consistent female predominance, but Asia-specific studies have found that the prevalence of IBS has no significant sex difference. [5][6][7][8] In alignment with the multiple apparent contributing pathogenic factors, management of IBS is multi-modal and includes pharmacological, neuromodulatory, dietary, psychological and other behavioral approaches. In Western countries such as those in North America, Australia, New Zealand, and Western Europe, there has been an increasing interest in utilising diet as a primary treatment modality rather than as an adjunct to pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) has a very high global incidence nowadays [1,2] . Though it is not fatal, it exerts a strong inf luence on the quality of human life [3] .…”
Section: Introductionmentioning
confidence: 99%